A novel scheduler for VBR traffic in IEEE 802.11 HCCA WLANs. (6th September 2011) - Kuo, Yaw-Wen; Tsai, Jin-Hsiu
IEEE 802.11 standard provides a reference scheduler with admission control, which is suitable for CBR traffic because the allocation of Transmission Opportunity (TXOP) duration is only based on the mean data rate. This paper proposes a novel scheduler for Variable Bit Rate (VBR) traffic, where the polling list and TXOP values are dynamically updated according to the current backlog and the measured loss rate of each flow. Moreover, an effective admission method is also provided as well to guarantee the loss rate. According to our simulation results, the number of admitted flows in the proposed scheduler is close to that in the reference scheduler and the loss rate can be well controlled below the threshold.